2021
DOI: 10.1038/s41598-021-83324-8
|View full text |Cite
|
Sign up to set email alerts
|

Dually nanocoated planar waveguides towards multi-parameter sensing

Abstract: The incidence of light on the edge of a glass coverslip for a microscope slide, deposited with a thin film on both faces, permits exciting two resonances in each polarisation state of the input light, TE and TM. This dually nanocoated waveguide can be used for detecting simultaneously two different parameters on the basis of a further deposition of suitable materials on each face. As an example, the possibility of detecting temperature and humidity by using polydimethylsiloxane and agarose coatings, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The sensing system exploits a recent, high-performance and super versatile physical phenomenon termed LMR, which is similar to surface plasmon resonance (SPR) in terms of mathematical description of electromagnetic fields, [48] but distinct in terms of the optical features from other well-investigated optical approaches, such as SPR, fiber gratings, and interferometry, with potentially remarkable advantages over the other optical detection approaches in terms of resonance tunability, sensitivity, figure of merit, and multiparameter sensing. [26,27] An elaborate fundamental study has showed the huge potentiality of LMR technology able to attain sensitivity in the order of tens of μm RIU À1 and resolution below 10 À7 RIU in aqueous environments. [49] Furthermore, in the proposed sensing system that has been envisaged by embedding the fiber within an ad hoc developed microfluidics, [30] the variation in the optical features of light depends solely on the changes in the RI of surrounding medium and not on other sources of noise like fiber deformation, temperature fluctuations, polarization effects (light polarization is fixed once LMR has been optimized), or source power fluctuations (wavelength-based detection is used).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensing system exploits a recent, high-performance and super versatile physical phenomenon termed LMR, which is similar to surface plasmon resonance (SPR) in terms of mathematical description of electromagnetic fields, [48] but distinct in terms of the optical features from other well-investigated optical approaches, such as SPR, fiber gratings, and interferometry, with potentially remarkable advantages over the other optical detection approaches in terms of resonance tunability, sensitivity, figure of merit, and multiparameter sensing. [26,27] An elaborate fundamental study has showed the huge potentiality of LMR technology able to attain sensitivity in the order of tens of μm RIU À1 and resolution below 10 À7 RIU in aqueous environments. [49] Furthermore, in the proposed sensing system that has been envisaged by embedding the fiber within an ad hoc developed microfluidics, [30] the variation in the optical features of light depends solely on the changes in the RI of surrounding medium and not on other sources of noise like fiber deformation, temperature fluctuations, polarization effects (light polarization is fixed once LMR has been optimized), or source power fluctuations (wavelength-based detection is used).…”
Section: Discussionmentioning
confidence: 99%
“…[23] LMR pinpoints improved detection flexibility and several advantages over well-established optical technology platforms based on other resonance-based phenomena, [26] such as a relatively easy tunability of the resonance wavelength over a wide spectral range from visible to near infrared (NIR) as a function of the coating thickness, the possibility of exciting both transverse electric (TE) and magnetic (TM) polarization states of light, and the capability of multiple LMR generation. [27] The combination of a special geometry of single-mode fibers, i.e., a D-shaped configuration, with additional nanometer-scale metal-oxide coating to support LMR, has offered remarkable results in terms of the limit of detection (LOD) of biomolecules in real samples. [21] Since tin dioxide (SnO 2Àx ) guaranteed an extremely high RI sensitivity in comparison with other LMR-generating nanomaterials, [26,28] this material has been used in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…The configuration consists of launching light on the edge of a coverslip for microscope glass slide, something successfully used for generation of LMRs by coating one face of the coverslip [19]. Moreover, it was recently demonstrated the ability to generate two independent LMRs in the same transmission spectrum by coating both faces of the coverslip [20], suggesting the possibility to generate a SPR and a LMR by deposition of a metallic thin film and a dielectric thin film. This is what will be done here: a silver and an ITO coating will be deposited on the same substrate to generate an SPR and an LMR with a single light source and spectrometer.…”
Section: 𝜺 Conditions N K Conditionsmentioning
confidence: 99%
“…LMRs can be generated on this type of substrate and easily polarized by using a linear polarizer. It has been demonstrated that using coverslips, instead of other glass planar substrates such as slides, allows the generation of LMRs with better characteristics such as resonance depth, a more directive coupling, and even the possibility of multiparameter detection [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%